Teacher professionalism development model as a pillar of elementary education quality - Ahmad Rifaudin; Bayu Pramono; Euis Asyiah; Encep Syarifudin; Eneng Muslihah (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
Teacher professionalism is a key factor in ensuring the quality of elementary education, particularly amid technological disruption and evolving global learning paradigms. This study explores an effective model for developing teacher professionalism to enhance basic education in Indonesia. Using a qualitative library research method, the study analyzes academic literature, policy documents, and recent research through data reduction, coding, comparison, and synthesis. Five existing models of teacher professional development were identified: conventional training-based, mentoring-based, practitioner community-based, digital technology-based, and integrated holistic models. Based on these, the study proposes the Continuous Integrative Teacher Professionalism Development Model (MPGIB), which integrates five essential components: development of pedagogical content knowledge (PCK) through practitioner communities, tiered mentoring, digital platforms, collaborative action research, and portfolio-based recognition. MPGIB offers a transformative approach, positioning teachers as reflective professionals with the autonomy for contextual self-development. Its implementation has implications for reforming teacher working groups (KKG/MGMP), optimizing professional development funds, strengthening evidence-based quality assurance, and redefining teachers as agents of educational change—ultimately contributing to improved teaching practices and the quality of basic education in Indonesia.